Students’ Attitudes towards Translation, their Difficulties and Use of Strategies in Vietnamese-English Translation - Trang, Nguyen Huynh (International Journal of Educational Technology and Learning, 2022)
Translation is a popular known job in today’s world and this has been explored by many studies in terms of strategies, knowledge and theoretical framework. In this study, the researcher aims to discover attitudes towards translation in respect to common difficulties and strategies used in translation. The study employed 29 students studying Business Translation at University of Economics Ho Chi Minh City. A questionnaire was designed based on the mixture of a five-point Likert scale and a yes-no question type. It uncovered that the majority of them confessed that they still have difficulties in using vocabulary including specialized terms and grammar. They also had an attitude that translation is interesting, and they need to read more in both English and Vietnamese for linguistic and stylish equivalence. Then, the majority of them found Google as a tool to help them solve translation strategies. Finally, the study also suggested some solutions and other solutions discussed in the related studies to tickling translation challenges.